Spontaneous Ovarian Hyperstimulation Syndrome in a Triplet Pregnancy - Nisha Rani Agrawal; Garima Gupta; Kusum Verma; Neeraj Varyani (Case Reports in Critical Care)
Ovarian hyperstimulation syndrome (OHSS) is a potentially life-threatening complication, usually iatrogenic after ovulation induction. OHSS is a very rare event in spontaneously conceived pregnancies. Only few cases have been reported in literature to the best of our knowledge. We report a very rare case of spontaneous critical OHSS (according to classification of severity of OHSS as mentioned in Greentop guidelines no. 5, 2006) associated with triplet pregnancy in a 26-year-old woman suffering from severe abdominal pain, distension, and dyspnea. Our case highlights the importance of a strong suspicion for OHSS when a clinical presentation could not be explained by common medical conditions.